Swim Bladder Disorders in Koi Carp (Cyprinus carpio) - Rubina Sirri; Luciana Mandrioli; Samuele Zamparo; Francesca Errani; Enrico Volpe; Giorgia Tura; Tim Barbé; Sara Ciulli (Animals, 2020)
Swim bladder disorders and consequent buoyancy problems are encountered in ornamental fish, including koi carp. Nevertheless, beyond clinical and pharmacological management, they are largely underdiagnosed. In this study, nine koi carp showing abdominal swelling and abnormal swimming behavior were investigated. Clinical approach, varying from case to case, included ultrasonographic and X-ray investigations, bacteriological analysis of the collected fluid, antimicrobial susceptibility pattern, and possibly histological analysis. Diagnostic imaging, corroborating gross examination, documented swim bladder deformation/dislocation and serous fluid within the swim bladder chambers of most animals. Bacteria belonging to the Aeromonas hydrophila/caviae group and Shewanella xiamenensis were identified. S. xiamenensis strains showed a sensibility to all tested molecules except for one strain, which was resistant to tetracycline and cyprofloxacin. Antibiotic treatment succeeded in the full recovery of three cases in which S. xiamemensis infection was detected. Chronic aerocystitis was histologically documented where tissue was available. The swim bladder histopathological findings highlighted a chronic process that had compromised the quality of life of the animals. A multidisciplinary clinical–pathological and microbiological approach is highly suggested to recognize swim bladder conditions as early as possible, aiming to drive medical intervention and raising the chances of fish survival.